The effect of total quality management, enterprise resource planning and the entrepreneurial orientation on the organizational performance: The mediating role of the organizational excellence --- A proposed research framework - Al-Dhaafri, Hassan Saleh; Yusoff, Rushami Zien; Al-Swidi, Abdullah Kaid (Sciedu Press, 2013)
Organizational performance and organizational excellence are the main two focuses of the management of any organization.In fact, the resources of an organization, either tangible or intangible, can distinguish the level of performance of one organization from its rivals. The question always is what are the key success factors that can enhance the organizational strategy implementation initiatives to produce value and create the competitive advantage. In today’s changing business environment, improvement and development of internal resources are very crucial to compete externally and globally. This paper aims to review the literature related to the organizational performance and explains the potential effects of TQM, ERP and EO.Given that not all the strategy implementation initiatives are fruitful, this paper attempted to establish an explanation of the mechanism through which such strategies can enhance the overall organizational performance.Based on a thorough review of the extant literature and the theoretical foundation, a research model was proposed.The proposed model is grounded by the fact that only excellent, innovative and differentiated companies and products can excite the customers and succeed in a turbulent business environment.